A Novel Efficient Certificateless Signature Scheme for the Prevention of Content Poisoning Attack in Named Data Networking-Based Internet of Things - Saddam Hussain; Syed Sajid Ullah; Abdu Gumaei; Mabrook Al-Rakhami; Ijaz Ahmad; Syed Muhammad Arif (IEEE Access)
Recently, Named Data Networking (NDN) has emerged as a popular and active Internet architecture that addresses the issues of current host-centric communication. NDN is well suited for Internet of Things (IoT) which possesses massive applications that dominate the Internet today. It intends to provide named-based routing, in-networking caching, built-in mobility and multicast support as part of its design which leads to a substantial improvement in content delivery/retrieval. Though, this new architecture aches from some new challenges in terms of security. In this article, we seek our attention towards Content Poisoning Attack (CPA). The purpose of CPA is to inject poisoned content with an invalid signature into the NDN-based IoT networks. Unfortunately, none of the existing proposals work effectively when malicious attackers compromise the caches of NDN routers. To prevent this, we proposed a certificateless signature scheme for the preservation of CPA in NDN-based IoT networks. The proposed scheme is formally secure under the security hardness of Hyperelliptic Curve Discrete Logarithm Problem (HCDLP) with a security simulation/validation in “Automated Validation of Internet Security Protocols and Applications (AVISPA).” Besides, the formal proof we also compared the designed scheme with some existing solutions to show the cost-efficiency in terms of communication overhead and computation cost. To conclude, a robust deployment on NDN-based IoT networks is shown.